Survival analysis of colorectal cancer patients with tumor recurrence using global score test methodology - Zain, Zakiyah; Aziz, Nazrina; Ahmad, Yuhaniz; Azwan, Zairul; Raduan, Farhana; Sagap, Ismail (2014)
Colorectal cancer is the third and the second most common cancer worldwide in men and women respectively, and the second in Malaysia for both genders.Surgery, chemotherapy and radiotherapy are among the options available for treatment of patients with colorectal cancer.In clinical trials, the main purpose is often to compare efficacy between experimental and control treatments. Treatment comparisons often involve several responses or endpoints, and this situation complicates the analysis. In the case of colorectal cancer, sets of responses concerned with survival times include: times from tumor removal until the first, the second and the third tumor recurrences, and time to death. For a patient, the time to recurrence is correlated to the overall survival.In this study, global score test methodology is used in combining the univariate score statistics for comparing treatments with respect to each survival endpoint into a single statistic. The data of tumor recurrence and overall survival of colorectal cancer patients are taken from a Malaysian hospital.The results are found to be similar to those computed using the established Wei, Lin and Weissfeld method. Key factors such as ethnic, gender, age and stage at diagnose are also reported.